Thermal-Aware Multiconstrained Intrabody QoS Routing for Wireless Body Area Networks. (16th March 2014) - Monowar, Muhammad Mostafa; Mehedi Hassan, Mohammad; Bajaber, Fuad; Hamid, Md. Abdul; Alamri, Atif
Abstract : Wireless body area networks (WBANs) can be formed including implanted biosensors for health monitoring and diagnostic purposes. However, implanted biosensors could cause thermal damages on human tissue as it exhibits temperature rise due to wireless communication and processing tasks inside the human body. Again, Quality of Service (QoS) provisioning with multiconstraints (delay and reliability) is a striking requirement for diverse application types in WBANs to meet their objectives. This paper proposes TMQoS, a thermal-aware multiconstrained intrabody QoS routing protocol for WBANs, with the aim of ensuring the desired multiconstrained QoS demands of diverse applications along with keeping the temperature of the nodes to an acceptable level preventing thermal damages. We develop a cross-layer proactive routing framework that constructs an ongoing routing table which includes multiple shortest-path routes to address diverse QoS requirements. To avoid the packets to traverse through heated areas known as hotspot, we devise a hotspot avoidance mechanism. The route selection algorithm of TMQoS selects forwarder(s) based on the intended QoS demands of diverse traffic classes. The performance of TMQoS has been evaluated through simulation which demonstrates that the protocol achieves desired QoS demands while maintaining low temperature in the network compared to the state-of-the-art thermal-aware approaches.